2022
DOI: 10.1108/ijbm-01-2022-0022
|View full text |Cite
|
Sign up to set email alerts
|

Surviving in financial advice deserts: limited access to financial advice and retirement planning behavior

Abstract: PurposeThis study introduces the concept of financial advice deserts (FADs), including financial advice received from personal financial advisors (PFAs) and Certified Financial Planners™ (CFP professionals) and investigates the association between living in these FAD states and the retirement planning activities of individuals.Design/methodology/approachThis study uses merged data gathered from multiple sources including (1) available state-level information on CFP professionals from the CFP board website, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Moreover, the coefficients on other variables are reasonable. For example, education level is positively related to propensity to hiring financial advisors, which is consistent with previous studies (Chatterjee & Zahirovic-Herbert, 2010;Collins, 2012). Marriage status is negative correlated with advice seeking, which is consist with study by Gutierrez et al (2011).…”
Section: Regression Analysissupporting
confidence: 91%
“…Moreover, the coefficients on other variables are reasonable. For example, education level is positively related to propensity to hiring financial advisors, which is consistent with previous studies (Chatterjee & Zahirovic-Herbert, 2010;Collins, 2012). Marriage status is negative correlated with advice seeking, which is consist with study by Gutierrez et al (2011).…”
Section: Regression Analysissupporting
confidence: 91%
“…Baeckström et al (2021) expresses that the literature establishes a causal link between a lack of trust and lower risk tolerances. Studies also point to a positive relationship between confidence and risk tolerance (Chatterjee et al, 2011). Salem (2019) found that low confidence and low-risk tolerance are seen together in his study on Arab women in Saudi Arabia and Jordan.…”
Section: H2: There Is a Positive Relationship Between Phantasy And Pl...mentioning
confidence: 94%
“…The positive association between cognitive ability and financial decision-making is well-established by past research. Studies have shown that higher cognitive ability is positively associated with financial outcomes, such as greater wealth [17][18][19][20][21], stock market participation [22,23], and financial planning [24]. Conversely, lower cognitive ability is associated with adverse financial behavior and outcomes, such as making more financial mistakes [6], having less financial knowledge [17], being less likely to participate in market recovery [25], and being more likely to default on mortgages [26].…”
Section: Cognitive Ability and Financial Decision-makingmentioning
confidence: 99%